PENGARUH BAHASA GAUL TERHADAP PENGGUNAAN BAHASA INDONESIA DALAM KOMUNIKASI SEHARI-HARI REMAJA DI LINGKUNGAN SEKOLAH - Rajagukguk, G. Emma; Sitepu, Dori Betsaida Br; Kaban, Ester Susmaita; Sitorus, Cristina Sitorus; Sitanggang, Vember Tri Rejeki Sitanggang; Putri, Anggia (Yayasan Panca Bakti Wiyata Pangandaran, 2025)
The use of slang among Indonesian teenagers has become increasingly popular, especially on social media and in daily life. While slang serves as a symbol of social identity, its excessive use can affect the ability to use correct and proper Indonesian, particularly in academic settings. This article examines the influence of slang on teenagers' Indonesian language skills, particularly in writing and speaking in formal school contexts. Through a literature review, it is found that while slang strengthens social bonds, uncontrolled usage can disrupt the ability to use standard Indonesian in formal situations. Therefore, it is important to find a balance between language creativity and the use of standard Indonesian in educational environments.